Cesarean delivery on child health and development in Japanese nationwide birth cohort - Naomi Matsumoto; Takashi Mitsui; Kei Tamai; Tomoya Hirota; Hisashi Masuyama; Takashi Yorifuji (Scientific Reports)
Abstract The long-term effects of cesarean delivery (CD) on child health and development remain controversial. This study aimed to investigate these effects using an outcome-wide approach in a Japanese context, where perinatal mortality rates are among the world’s lowest. We analyzed data from 2,114 children in a nationwide Japanese birth cohort, linking the 21st Century Longitudinal Survey of Newborns with the Perinatal Research Network database. We examined associations between CD and various health and developmental outcomes up to 9 years of age, including hospitalizations, obesity, and developmental milestones. After adjusting for potential confounders, CD was not significantly associated with most outcomes, including all-cause hospitalization (adjusted risk ratio 1.25, 95% CI 0.997–1.56), obesity at 5.5 and 9 years, and various developmental milestones. Subgroup analyses for multiple births and preterm infants showed some differences in point estimates, but were limited by small sample sizes. CD was not significantly associated with adverse long-term child health or developmental outcomes in this Japanese cohort. These findings provide reassurance regarding CD safety when medically indicated in advanced perinatal care settings. Further research with larger samples and longer follow-up is needed, especially for specific subgroups.